Alea Ke Pau or Negotiated Evaluation: A Vital Concept in Pacific Health Promotion - Ofanoa, Malakai; Ofanoa, Samuela; Buetow, Stephen (Advances in Social Sciences Research Journal, 2021)
For Pacific peoples, health promotion, community nursing and community development initiative over many years, has often been conducted within a framework of one-sided decision-making. There is always an imbalance between the power relationships of the community being studied and those of the researchers or health practitioners. As a result, there is lack of understanding on the part of the researchers and the health funding agencies of the need to negotiate processes with members of the community being studied or engaging with. All of this are within an overarching lack of understanding of, and respect for, Pacific cultural values, frameworks and Pacific ways of doing things. This paper seeks to explore an alternative concept whereby these values are acknowledged. This concept is metaphorically called “alea ke pau” (or, negotiated evaluation). This approach is forward-looking and one that respects a ‘bottom-up’ view rather than the traditional ‘top-down’ view of health work and funding agencies. However, using two Pacific research methodologies called Talanga and Kakala, to explore the concept of alea ke pau were held with five men’s focus groups operating within Kava Clubs in Auckland, New Zealand, and five focus groups in Tonga. The results from these discussions are presented demonstrating the development and application of the “alea ke pau” or “negotiated evaluation” approach.